Randomised phase II trial of trofosfamide vs. doxorubicin in elderly patients with untreated metastatic soft-tissue sarcoma. (January 2020) - Hartmann, Joerg T.; Kopp, Hans-G.; Gruenwald, Viktor; Piperno-Neumann, Sophie; Kunitz, Annegret; Hofheinz, Ralf; Mueller, Lothar; Geissler, Michael; Horger, Marius; Fix, Peter; Chemnitz, Jens M.; Neise, Michael; et al.
Abstract: Doxorubicin represents the standard first-line treatment for metastatic soft-tissue sarcoma. We assessed the efficacy and safety of trofosfamide in elderly patients. In this controlled phase II trial, we randomly (1:2) assigned 120 previously untreated patients with soft-tissue sarcoma, older than 60 years, with an Eastern Cooperative Oncology Group score of 0–2, to receive either doxorubicin for 6 cycles (arm A) or oral trofosfamide (arm B). The primary end-point was a 6-month progression-free rate (PFR) in the experimental arm (clinical trial information: NCT00204568). Between August 2004 and October 2012, forty and 80 patients were randomly assigned to arm A and arm B, respectively, in 16 centres. The median age was 70 years (range, 60–89). The primary study end-point (6-month PFR) was exceeded, with 27.6% in arm B (95% confidence interval [CI], 18.0–39.1) and 35.9% in arm A: (95% CI, 21.2–52.8). Survival data in terms of progression-free survival were 4.3 months (95% CI, 2.2–6.3) and 2.8 months (95% CI, 1.7–3.6) and in terms of overall survival were 9.8 months (95% CI, 6.7–11.6) and 12.3 months (95% CI, 9.6–16.2), respectively. The number of serious adverse event (SAE) was 59% in arm A and 30.3% in arm B (p = 0.005). Trofosfamide caused more often dyspnoea and low-grade fatigue, whereas with doxorubicin, more often leukocytopenia, neutropenia and mucositis were seen. Discontinuation rates for reasons other than disease progression were 15.4% (arm A) vs. 7.9% (arm B). In an elderly population of patients, oral trofosfamide achieved the estimated primary end-point 6-month PFR and was associated with a favourable toxicity profile compared with doxorubicin. Highlights: No specific studies are available for elderly metastatic sarcoma patients. This randomised phase 2 trial mets the defined primary endpoint 6-mos PFR. The number of serious adverse events was lower in the trofosfamide arm. Discontinuation rates other than disease progression were in favour of trofosfamide. Trofosfamide might be an alternative in elderly metastatic sarcoma patients.